1989
DOI: 10.1073/pnas.86.21.8412
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets in smooth muscle cell proliferation and migration after vascular injury in rat carotid artery.

Abstract: Intimal Platelets are thought to play a major role in the formation of arterial intimal lesions (1, 2) by releasing, at sites of endothelial denudation, growth factors that stimulate smooth muscle cell (SMC) growth. Support for the role of platelets in vivo comes from the key study of Friedman et al. (3), in which these authors showed that experimentally induced intimal lesion formation in rabbit arteries was significantly inhibited by prolonged thrombocytopenia. This study was interpreted by others to suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
147
1
5

Year Published

1993
1993
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 373 publications
(157 citation statements)
references
References 22 publications
4
147
1
5
Order By: Relevance
“…32,33 The response to thrombin in mouse and rat platelets appears to be mediated by PAR-3 and PAR-4, 42,43 2 distinct protease-activated thrombin receptors. Because platelet adhesion, aggregation, and degranulation are important components of the vascular injury process, 44,45 these plateletdependent processes would not be affected in PAR-1-deficient mice. Therefore, our mouse model does not assess the contribution of thrombin-induced platelet aggregation to the vascular injury response.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 The response to thrombin in mouse and rat platelets appears to be mediated by PAR-3 and PAR-4, 42,43 2 distinct protease-activated thrombin receptors. Because platelet adhesion, aggregation, and degranulation are important components of the vascular injury process, 44,45 these plateletdependent processes would not be affected in PAR-1-deficient mice. Therefore, our mouse model does not assess the contribution of thrombin-induced platelet aggregation to the vascular injury response.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular smooth muscle cell (VSMC) 1 proliferation and migration are associated with several vascular diseases such as atherosclerosis and restenosis following vascular injury (1)(2)(3)(4)(5). VSMC from several species when cultured in vitro undergo a change in phenotype from a contractile state to a synthetic state similar to the changes that occur with VSMC in vivo in response to vascular injury (6 -8).…”
mentioning
confidence: 99%
“…We have previously shown that platelet depletion inhibits intimal thickening in balloon-injured rat arteries but does not affect SMC replication, suggesting that platelets stimulate migration. 4 Data are now beginning to emerge that suggest that platelet-derived growth factor (PDGF) may be an important mediator of migration. Administration of exogenous PDGF to rats causes a marked stimulation of intimal SMC accumulation 5 but has little effect on the replication rate of these cells.…”
mentioning
confidence: 99%